FACTORS OF DEBRISFLOW ORIGINATION IN THE SOUTH-WEST AREA OF LAKE BAIKAL - Laperdin, Valerii Kirillovich (European Scientific Journal, ESJ, 2014)
The structure of mud-rock streams (debris flow) in the south of Baikal region, as well as the recurrence of events, depend on the seismic and tectonic activity, morphology and relief (difference in elevation in the small area between the Lake Baikal‘s brink and the watershed, diverse geological structure of solid rocks, their physical-mechanical and physical-chemical characteristics in relation to weathering agents, as well as the degree of rock crush; peculiarities of heat- and humidity conditions in the area (the rates and distribution of atmospheric precipitation, according to season, elevation zones and within the long-term cycle.